EFEKTIVITAS OZONATED VIRGIN COCONUT OIL TERHADAP PENYEMBUHAN LUKA FULL THICKNESS SKIN GRAFT AUTOLOG TIKUS SPRAGUE DAWLEY Ditinjau dari Ekspresi TGF-? dan Jumlah Neutrofil - Kusuma, Nauval Marta; Hardian, Hardian; Najatullah, Najatullah; Yuniati, Renni; Susilaningsih, Neni (Medica Hospitalia : Journal of Clinical Medicine, 2021)
Abstract Introduction : Skin grafts are now one of treatment option in wound healing process that is always developing. TGF-bexpression and the number of neutrophils have an important role in healing skin graft wounds. Ozone (O3) has disinfecting properties that are effective in wound healing. Objective : Proving the effectiveness of Ozonated VCO for Full Thickness Skin Graft wound healing using parameter of TGF-b expression and neutrophil number. Method : This study is an experimental study with a post-test only design group of 40 Sprague Dawley rats performed autologous skin graft at the same time. Samples were divided randomly into 8 groups (K1 = without Ozonated VCO), (A1 = Ozonated VCO 50 mg / ml), (B1 = Ozonated VCO 100 mg / ml), (C1 = Ozonated VCO 200 mg / ml), ( K2 = without Ozonated VCO) (A2 = Ozonated VCO 50 mg / ml), (B2 = Ozonated VCO 100 mg / ml), (C2 = Ozonated VCO 200 mg / ml). Assessment of TGF-b expression and neutrophil number of tissue was performed by staining hematoxylin & eosin and immunohistochemistry on days 6 and 12 after skin graft. Results : There were significant differences (p <0.05) TGF-b expression and neutrophils number of tissue between the control group and the administration of Ozonated VCO doses of 50 mg / ml, 100 mg / ml and 200 mg / ml on days 6 and 12 post skin graft. Conclusion : The administration of Ozonated VCO effectively improve Full Thickness Skin Graft wound healing seen from macroscopic wounds, increase TGF-b expression and decrease the number of neutrophils.